Association of Neutrophil Activation, More Than Platelet Activation, With Thrombotic Complications in Coronavirus Disease 2019. (6th December 2020) - Petito, Eleonora; Falcinelli, Emanuela; Paliani, Ugo; Cesari, Enrica; Vaudo, Gaetano; Sebastiano, Manuela; Cerotto, Vittorio; Guglielmini, Giuseppe; Gori, Fabio; Malvestiti, Marco; Becattini, Cecilia; Paciullo, Francesco; et al.
Abstract: Background: Severe acute respiratory syndrome coronavirus 2 infection is associated with hypercoagulability, which predisposes to venous thromboembolism (VTE). We analyzed platelet and neutrophil activation in patients with coronavirus disease 2019 (COVID-19) and their association with VTE. Methods: Hospitalized patients with COVID-19 and age- and sex-matched healthy controls were studied. Platelet and leukocyte activation, neutrophil extracellular traps (NETs), and matrix metalloproteinase 9, a neutrophil-released enzyme, were measured. Four patients were restudied after recovery. The activating effect of plasma from patients with COVID-19 on control platelets and leukocytes and the inhibiting activity of common antithrombotic agents on it were studied. Results: A total of 36 patients with COVID-19 and 31 healthy controls were studied; VTE developed in 8 of 36 patients with COVID-19 (22.2%). Platelets and neutrophils were activated in patients with COVID-19. NET, but not platelet activation, biomarkers correlated with disease severity and were associated with thrombosis. Plasmatic matrix metalloproteinase 9 was significantly increased in patients with COVID-19. Platelet and neutrophil activation markers, but less so NETs, normalized after recovery. In vitro, plasma from patients with COVID-19 triggered platelet and neutrophil activation and NET formation, the latter blocked by therapeutic-dose low-molecular-weight heparin, but not by aspirin or dypiridamole. Conclusions: Platelet and neutrophil activation are key features of patients with COVID-19. NET biomarkers may help to predict clinical worsening and VTE and may guide low-molecular-weight heparin treatment. Abstract : Platelets and neutrophils are activated in patients with coronavirus disease 2019. Increased neutrophil extracellular trap biomarkers are particularly associated with venous thromboembolism thrombotic events and may help predict clinical worsening and venous thromboembolism and guide low-molecular-weight heparin treatment.